Rekrutmen, Seleksi Dan Penempatan (Manajemen Sumber Daya Manusia) - Aziza S (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Recruitment is the process of finding and attracting applicants to be placed in positions or jobs in and by an organization or company. This process starts when applicants are sought and ends when their applications are submitted. The result is a collection of jobseekers to be selected. Selection is an effort made to choose and get workers who have the ability in accordance with the tasks that will be done in an empty position to be filled and occupied. The conformity basically can be known by referring to the job / position description that has been made. Next thing that must be done immediately is placement. Placement is the assignment or reassignment of an employee to his new job.